APPLICATION OF MATHEMATICAL STATISTICS METHODS FOR FORECASTING THE NUMBER OF CUSTOMS DECLARATIONS - Lebid, V. V.; Meish, Yu. A.; Maiborodina, N. V.; Herasymenko, V. P. (Systems and Technologies, 2022)
The paper deals with the issue of forecasting the number of completed customs declarations using the methods of mathematical statistics. The main goal of this work is to forecast the number of possible customs declarations of the MD-2 form in conditions of uncertainty based on the available statistical data for previous years. Statistical observations on the volume of foreign trade in goods are carried out on the basis of submitted customs declarations, which are filled out by declarants during customs clearance of goods. Customs statistics is one of the important branches of detailed information on goods moving across the customs border of Ukraine, the purpose of their movement, and information for control and assessment of customs payments, which is carried out thanks to completed customs declarations. Statistical reports of enterprises and organizations of Ukraine on the export-import of goods that are not subject to customs declaration play an important role in keeping statistics. The customs declaration becomes the primary document that confirms important indicators for statistical data after it is checked by a customs representative, so forecasting the number of such declarations becomes an important issue when planning the country’s foreign trade volumes. Regression functions of the volume of completed customs declarations of the MD-2 form and the volume of completed customs declarations of the MD-2 form according to the electronic declaration procedure using the Microsoft Excel spreadsheet processor were built on the basis of statistical data of customs declaration statistics in this paper. Important components of the success of the research are the correct formulation of the problem, the possibility of further interpretation of the obtained results, as well as the logically correct formal application of the existing mathematical apparatus. The study of the reliability of the results obtained in the work was conducted and the reliability of the constructed regression functions was proved. Constructed reliable regression functions make it possible to forecast the volume of completed customs declarations for 2023. The results obtained in this study play an important role in planning the volume of foreign and domestic trade in goods and analyzing the receipts of customs payments to the State Budget of Ukraine for 2023.